2014
DOI: 10.1097/paf.0000000000000081
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dactyloscopic Powders on DNA Profiling From Enhanced Fingerprints

Abstract: We conducted a study on the effect of fingerprint enhancement methods on subsequent short tandem repeat profiling. First, we performed a study typing blood traces deposited on 5 different surfaces, treated with 8 types of dactyloscopic powders. Three different DNA extraction methods were used. Subsequently, we analyzed latent fingerprints on the same 5 surfaces enhanced with the 8 different powders used in the first part of the study. This study has demonstrated that DNA profiling can be performed on fingerpri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 17 publications
1
9
0
2
Order By: Relevance
“…Importantly, these two groups did not use the newly formulated STR amplification kits more tolerant to PCR inhibition. DNA degradation was also invoked as a potential effect of "magnetic powder" [23] but this effect was not observed in the study presented herein.…”
Section: Page 17 Of 25mentioning
confidence: 87%
“…Importantly, these two groups did not use the newly formulated STR amplification kits more tolerant to PCR inhibition. DNA degradation was also invoked as a potential effect of "magnetic powder" [23] but this effect was not observed in the study presented herein.…”
Section: Page 17 Of 25mentioning
confidence: 87%
“…With fingermarks enhancement, several studies [49][50][51][52][53][54] have shown that most of the reagents commonly used to develop latent marks, such as aluminium powder, black magnetic powder, fluorescent powders, wet powder suspension and 1,2-indanedione do not affect subsequent recovery of DNA. Other specific chemicals such as cyanoacrylate and ninhydrin may have a negative impact on the process as they can either degrade or sequester the DNA or inhibit the PCR reaction [55,56].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The effect of fingerprint powders on subsequent DNA analysis has been well documented over the last 15 years . The majority of studies have looked at the impact of fingerprint powders on subsequent DNA analysis, with a focus on: the effect of various substrates ; the quality of fingerprints ; the effect of time ; the effect of materials routinely used in forensic investigations ; and various fingerprint treatments .…”
mentioning
confidence: 99%
“…There are only a few studies published comparing multiple DNA extraction techniques for various types of fingerprint powder . Lin et al .…”
mentioning
confidence: 99%
See 1 more Smart Citation